RAGAM PROFESIONALISME GURU BIMBINGAN DAN KONSELING ZAMAN NOW - M. Adi Putra Ap; Nurida Shofiria (Jurusan Bimbingan dan Konseling, 2019)
Teacher Guidance and Counseling in the present day must have a strong foundation of educational science, because the Counselor is one of the types of education personnel in the Law of the Republic of Indonesia Number 20 of 2003. In line with the recognition of government policy counselors in developing the quality of teacher Guidance and Counseling. Teacher certification policy is expected to be able to improve the quality of teacher professionalism Counseling Guidance / Counselor. However, teacher certification did not have a significant impact on improving the professionalism of teacher guidance and counseling, there are still many teachers who have low UKG Counseling / Counselor scores, there are still many Teachers Counseling Guidance / low quality quality counselors and the lack of scientific work contributions generated by teachers Counseling Guidance / Counselors Therefore, it is necessary to have various forms of professional improvement in Guidance and Counseling Teachers so as to increase the choice of Counseling / Counselor Guidance methods in developing Skills professionalism. In developing the professionalism of the Counseling / Counselor Guidance there are several methods, methods in the form of education and training and not education and training, and to realize a truly professional and competent teacher is not enough to follow the PLPG / PPG certification program, the government must have a program continued after the teacher Counseling / Counselor Guidance has a professional certificate to maintain and uplift knowledge according to the times, there are dimensions that must be fulfilled so that the professionalism is maintained, guarantees and always increases in accordance with the needs and demands that develop, among others, with Continuing Professionality Development). Facilitated Counseling / Counseling Teachers and routinely carrying out Continuous Professional Development will certainly show very significant results in the development of Counseling / Counseling Teacher Skills so as to add insight, skills and competencies in today's era.